Physical and Thermophysical Properties of Materials Based on Mineral and Vegetable Raw Materials - Abidjon, Tillayev; Haqberdi, Berdiyev (European Journal of Life Safety and Stability (2660-9630), 2022)
Numerous studies have established that one of the ways to rationally use agricultural waste is to use it as a heat-insulating and heat-insulating structural building material; in most cases, this applies to low-rise and, especially, rural construction. In this case, mineral and organic binders can be used as binders. The problems of obtaining such materials were mainly solved. There are no studies of physicochemical, physic technical, incl. and pyrotechnic properties of agricultural waste, especially cotton stalks and materials based on them, and the operational and technical properties of structures using of these materials, which makes it difficult to predict the long-term preservation and, accordingly, ensure the thermal comfort of residential buildings in the sharply continental climatic conditions of the Republic of Uzbekistan.